Handbook of Printed Circuit Manufacturing - Clark, Raymond H. author. aut Link
XIX, 620 p.
Keywords: Of all the components that go into electronic equipment, the printed circuit probably requires more manufacturing operations-each of which must be per formed by a skilled person-than any other. As a shift supervisor early in my printed circuit career, I had to hire and train personnel for all job functions. The amount of responsibility delegated to my subordinates depended strictly on how well I had been able to train them. Training people can be a trying experience and is always a time-consuming one. It behooved me to help my workers obtain the highest degree of job under standing and skill that they and I were capable of. One hindrance to effective teaching is poor continuity of thought, for example, having to say to a trainee, "Wait a minute; forget what I just told you. We have to go back and do some thing else first. " It was in trying to avoid pitfalls such as this that I undertook a detailed examination of the processes involved, what I thought each trainee had to know, and what questions they would most frequently ask. From this analysis I developed the various process procedures. Only after I had done so was I able to train effectively and with the confidence that I was doing the best possible job. Answers had to be at hand for all of their questions and in what ever detail they needed to know.